2015
DOI: 10.1016/j.ijheatmasstransfer.2015.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the lifetime of droplets emitted from mechanical cooling towers by numerical investigation

Abstract: A numerical modelling capable to simulate the drift and the evaporation of water droplets emitted by a mechanical cooling tower in an urban area is presented. The model is based on a real mechanical draft cooling tower situated in the surroundings of the Miguel Hernández University (Elche, Spain). An experimental study of the deposition of droplets from the cooling tower is done in order to validate the numerical modelling. This study is performed by means of the water sensitive papers technique. A biharmonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
(13 reference statements)
1
3
0
Order By: Relevance
“…Meanwhile, the measured deposition was used for validating their numerical model. Results from the study of Sánchez et al [125] were broadly consistent with those of Lucas et al [97]; they revealed that a short lifetime is favored under conditions with high ambient temperature, low relative humidity and small droplet size.…”
Section: Cooling Tower Driftsupporting
confidence: 76%
See 1 more Smart Citation
“…Meanwhile, the measured deposition was used for validating their numerical model. Results from the study of Sánchez et al [125] were broadly consistent with those of Lucas et al [97]; they revealed that a short lifetime is favored under conditions with high ambient temperature, low relative humidity and small droplet size.…”
Section: Cooling Tower Driftsupporting
confidence: 76%
“…Sánchez et al [125] studied the lifetime of drift with the combined effects of atmospheric conditions and droplet size distribution. If the lifetime experienced by the droplets is less than the time necessary to reach ground level, there is obviously less risk of Legionella bacteria.…”
Section: Cooling Tower Driftmentioning
confidence: 99%
“…from a kitchen exhaust) and spread to the same building at different positions [13 , 14] , like the possible SARS spreading in typical HRR buildings in Hong Kong [15][16][17] . Pollutants may also be released from sources located around a HRR building at lower levels [18][19][20][21][22] , such as the evaporative facilities (e.g. cooling tower or air scrubber) of public facilities, which have been responsible for reported disease outbreaks [23][24][25] .…”
mentioning
confidence: 99%
“…Based on a sensitivity analysis of plume rise heights from cooling towers, Ding et al [14] discovered that the primary determinant of plume rise height is the stability of the atmosphere around the cooling tower. Sánchez et al [15] presented a numerical model capable of simulating the drift and evaporation of water droplets emitted by a mechanical cooling tower, which revealed the influence of external conditions on droplet lifetime.…”
Section: Introductionmentioning
confidence: 99%